Ten Years Evaluation of the Relationship Between the Individual Dose of Hospital Workers Occupationally Exposed to X-Rays and its Leukocyte and Platelet Counts of the CBC Tests - Rochelle Lykawka; Alexandre Bacelar; Fábio Fernandes Dantas Filho; Milena Ávila Peres; Juliana Ávila Duarte (Brazilian Journal of Radiation Sciences)
The occupational health assessment of workers exposed to ionizing radiation is done through Complete Blood Count (CBC) tests in some countries, although studies have shown that this biomarker does not show evidence of exposition to low dose radiation. It is essential to analyze the radiation level doses of healthcare workers (HCW) exposed to X-rays in a university hospital and evaluate the association of this exposure on blood exam parameters. For this purpose, CBC tests and individual records of the X-rays exposure of 766 HCW were retrospectively evaluated from 2009 to 2019. Analyzing the annual and the monthly individual effective doses, no statistically significant relationship was identified with leukocyte count (b = -0.01 (95% CI, -0.03 - 0.01); p = 0.254) and (b = -0.04 (95% CI, -0.02 - 0.12); p = 0.606) respectively; nor for platelet count (b = -0.52 (95% CI, -1,09 - 0.05); p = 0.072) and (b = -0.69 (95% CI, -3.63 - 2.25); p = 0.646), respectively. Assessing the relationship between the monthly dose and the CBC tests, we found association with the leukocyte count (b = -0.12 (95% CI, -0.19 - -0.04); p = 0.002), but did not occur for platelet count (b = -1.91 (95% CI, -4.93 - 1.11); p = 0.215).  The findings of the study demonstrated that there is no statistically significant relationship, with regard to clinical validity, between the individual effective doses and the leukocyte and platelet count in the CBC test in all analyses performed.